2016
DOI: 10.12944/cwe.11.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting the Stability of OB Dump by Using Fly Ash: A Geo Technical Approach to Sustainably Manage OB Dump at Jharia Coalfield, India

Abstract: This paper is mainly focused over the possible utilization of fly ash along with OB dump to enhance the stability of OB dump and thus provide a sustainable approach for better waste management of both these materials simultaneously. Instability of coal mine overburden (OB) dumps is an important problem in most of the coal mines like Jharia coalfields in India. This is mainly occurring due to sliding nature of the rock material, lack of vegetation etc. Numbers of Environmental and health issues are associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Rajak et al [56] identified the surface characterization of materials of fly ash (Class F) and OB material using scanning electron microscope (SEM) test and found that OB material has irregular shape however, fly ash has spherical shape. The addition of fly ash in OB material provides the good packaging and bonding which improves the stability of the dump [57].…”
Section: Integration Of Fly Ash With Ob Dump Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rajak et al [56] identified the surface characterization of materials of fly ash (Class F) and OB material using scanning electron microscope (SEM) test and found that OB material has irregular shape however, fly ash has spherical shape. The addition of fly ash in OB material provides the good packaging and bonding which improves the stability of the dump [57].…”
Section: Integration Of Fly Ash With Ob Dump Materialsmentioning
confidence: 99%
“…Stability analysis of the fly ash mixed mine OB dump materials revealed that 20-25% fly ash can be utilized for stabilizing the dump [58]. Gupta and Paul [57] suggested that 10-20% fly ash can be used to enhance the strength of the OB dump. Rajak et al [56] have evaluate the shear strength parameters of OB material mixed with fly ash (Class F) with and without addition of Ground Granulated Blast Furnace Slag (GGBS) and found that addition of 20% fly ash with OB material causes improvement in cohesion value by 45%.…”
Section: Shear Strength Characteristicsmentioning
confidence: 99%
“…It has been noted by Gupta and Paul [23] that slope geometry and the strength of materials on it ultimately determines the stability of a slope. Table 2 shows that the range of the angle of internal resistance and cohesion of the slope materials are 8°-37° and 13-34kN/ m 2 respectively.…”
Section: Tailing Geotechnical Propertiesmentioning
confidence: 99%
“…The addition of fly ash in the OB dump material changes its shear strength behaviour thereby affecting the stability of dumps. Limited research has been carried out to assess the effect of mixing the fly ash with OB dump material on its slope stability (Singh 2011, Jayanthu et al 2012, Pradhan et al 2014, Gupta and Paul 2016, Dewangan et al 2016. Singh (2011) studied the effect of mixing 30% fly ash on factor of safety for OB dump slope of a height of 120 m under dry and wet conditions using numerical simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Pradhan et al (2014) also analyzed the stability of dump slope of 60 m height having an overall slope angle of 32° made up of OB dump material randomly mixed with 20% fly ash by weight and found the slope stable. Gupta and Paul (2016) conducted direct shear tests on OB dump material mixed with 10%, 20% and 30% fly ash by weight and concluded that mixing of fly ash in the range of 10% to 20% by weight improves the shear strength of the mixture. The limitations of all the above studies were the inclusion of only sand and silty fractions of …”
Section: Introductionmentioning
confidence: 99%